Efficacy of intratympanic steroid in the management of sudden sensorineural hearing loss: a prospective clinical study - Solanki, Karnadev J.; Ghodasara, Sonali D.; Bhatasana, Anand J. (International Journal of Research in Medical Sciences, 2025)
Sudden sensorineural hearing loss (SSNHL) is a distressing otologic emergency that requires prompt management. Systemic corticosteroids have traditionally been the mainstay of treatment; however, concerns regarding systemic side effects and contraindications have led to increasing interest in intratympanic steroid (ITS) therapy. Objectives were to evaluate the efficacy of intratympanic dexamethasone in patients with SSNHL. It was a prospective, nonrandomized multicenter clinical trial. Patients diagnosed with unilateral SSNHL received intratympanic dexamethasone injections and were evaluated using serial pure tone audiometry. Hearing outcomes were assessed by changes in pure tone average (PTA). Clinically significant hearing improvement (>10 dB PTA gain) was observed in 83% of patients. Greater hearing recovery was noted in patients treated earlier after symptom onset. Intratympanic dexamethasone is a safe and effective treatment option for SSNHL and may be considered as a primary treatment modality, particularly when initiated early.